Full gan asymmetrical half-bridge pwm converter with synchronous rectifier for a high efficient 90 W laptop charger - Kohlhepp, Benedikt; Zeller, Valentin; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Since modern semiconductors, like GaN-and SiC-devices, provide superior characteristics over conventional Si-devices, their contribution to a DC/DC converter is studied here. First, the paper describes two different simulation models for the asymmetrical half-bridge converter. Based on this, a proper simulation routine is used to find an optimized design for a given specification using GaN-devices for the half-bridge and the synchronous rectifier. After that, a practical test setup validates the simulation results and shows superior performance compared to converters built with conventional Si-devices. The full GaN converter features higher power density as well as higher efficiency.
CRIS-Team Scopus Importer:2021-11-05